Impact of Psychiatric Diagnosis and Treatment on Medication Adherence in Youth With Systemic Lupus Erythematosus. Issue 1 (30th December 2020) - Chang, Joyce C.; Davis, Alaina M.; Klein‐Gitelman, Marisa S.; Cidav, Zuleyha; Mandell, David S.; Knight, Andrea M.
Abstract : Objective: Youth with systemic lupus erythematosus (SLE) experience high rates of psychiatric comorbidities, which may affect medication adherence. We undertook this study to examine the association between psychiatric disorders and hydroxychloroquine adherence and to determine whether psychiatric treatment modifies this association. Methods: We identified incident hydroxychloroquine users among youth with SLE (ages 10–24 years) using de‐identified US commercial insurance claims in Optum Clinformatics Data Mart (2000–2016). Adherence was estimated using medication possession ratios (MPRs) over a 365‐day time period. Multivariable linear regression models were used to estimate the effect of having any psychiatric disorder on MPRs, as well as the independent effects of depression, anxiety, adjustment, and other psychiatric disorders. We tested for interactions between psychiatric diagnoses and treatment with psychotropic medications or psychotherapy. Results: Among 873 subjects, 20% had a psychiatric diagnosis, most commonly depression. Only adjustment disorders were independently associated with decreased MPRs (β –0.12, P = 0.05). We observed significant crossover interactions, in which psychiatric disorders had opposite effects on adherence depending on the receipt of psychiatric treatment. Among youth with any psychiatric diagnosis, psychotropic medication use was associated with a 0.15 increase in the MPR compared with no psychotropic medication use ( P = 0.02 for interaction). Among youth with depression or anxiety, psychotherapy was also associated with a higher MPR compared with no psychotherapy ( P = 0.05 and P < 0.01 for interaction, respectively). Conclusion: The impact of psychiatric disorders on medication adherence differed by whether youth had received psychiatric treatment. Improving recognition and treatment of psychiatric conditions may increase medication adherence in youth with SLE.